Accuracy of preoperative CT T staging of renal cell carcinoma: which features predict advanced stage?. Issue 8 (August 2015) - Bradley, A.J.; MacDonald, L.; Whiteside, S.; Johnson, R.J.; Ramani, V.A.C.
<x xml:space="preserve">Abstract</x> Aims To characterise CT findings in renal cell carcinoma (RCC), and establish which features are associated with higher clinical T stage disease, and to evaluate patterns of discrepancy between radiological and pathological staging of RCC. Materials and methods Preoperative CT studies of 92 patients with 94 pathologically proven RCCs were retrospectively reviewed. CT stage was compared with pathological stage using the American Joint Committee on Cancer (AJCC), 7th edition (2010). The presence or absence of tumour necrosis, perinephric fat standing, thickening of Gerota's fascia, collateral vessels were noted, and correlated with pT stage. The sensitivity, specificity, and positive (PPV) and negative predictive values (NPV) for predicting pT stage ≥pT3a were derived separately for different predictors using cross-tabulations. Results Twenty-four lesions were pathological stage T1a, 21 were T1b, seven were T2a, 25 were T3a, 11 were T3b, four were T3c, and two were T4. There were no stage T2b. Sixty-three (67%) patients had necrosis, 27 (29%) thickening of Gerota's fascia (1 T1a), 25 had collateral vessels (0 T1a), 28 (30%) had fat stranding of <2 mm, 20 (21%) of 2–5mm and one (1%) of >5 mm. For pT stage ≥pT3a, the presence of perinephric fat stranding had a sensitivity, specificity, PPV and NPV of 74%, 65%, 63%, and 76%, respectively. Presence of tumour necrosis had a sensitivity, specificity, PPV, and NPV of 81%, 44%, 54%, and 72%, respectively. Thickening of Gerota's fascia had a sensitivity, specificity, PPV, and NPV of 52%, 90%, 81% and 70%, respectively; and enlarged collateral vessels had a sensitivity, specificity, PPV, and NPV value of 52%, 94%, 88%, and 71% respectively. Conclusion The presence of perinephric stranding and tumour necrosis were not reliable signs for pT stage >T3a. Thickening of Gerota's fascia and the presence of collateral vessels in the peri- or paranephric fat had 90% and 94% specificity, with 82% and 88% PPV, respectively, for the presence of tumour stage for pT stage >T3a. These are considered reliable signs of locally advanced renal cancer.